KONSEP AKHLAK MAHMUDAH DAN MADZMUMAH PERSPEKTIF HAFIDZ HASAN AL- MAS’UDI DALAM KITAB TAYSIR AL-KHALLAQ - Ali Mustofa; Fitria Ika Kurniasari (Ilmuna: Jurnal Studi Pendidikan Agama Islam, 2020)
Improving morals, morals, and human character is obligation for human being, which aimed to achieve their life goals, such as realizing Insan kamil (perfect human). Moral is the main thing for humans, therefore the Prophet told his ummah to improve morals more and more. This study found that: morals means behavior, character, behavior or trait. According to al-Ghazali, moral is a trait that is embedded in the human soul which gives birth to easy human actions without need for thought or consideration. Taysir Al-Khallaq means a book that makes it easy for someone to carry out morals and understand the kinds of morals. So knowing the morals certainty must be implemented abandoned. The results of this study are according to Hafidz Hasan al-Mas'udi in the Taisiirul Khollaq Fi Fi Ilmil Akhlaq giving a concept of how we have the Mahmudah character, and go away from the Madzmumah character, such as hasud, arrogance, revenge, this is a trait that we must stay away from as educators or students. Meanwhile, honesty, humality, tawadhu are trait must be owned. The conclusion is the concept of moral education which is included in attitudes or behaviors are the relationship with Allah, oneself, attitudes and family.